Current Problems Faced by Russia in the State-Legal Policy in Social Partnership in the Labor Field - BAIEVA, Nataliya Anatolyevna; BURKIN, Dmitriy Olegovich; VYSHESLAVOVA, Tatyana Fedorovna; LUKINOVA, Svetlana Alekseevna (Journal of Advanced Research in Law and Economics, 2018)
In this article, the authors consider the basics of Russia’s current state-legal policy pursued in the field of social partnership, analyze basic international legal and national statutory and legal acts, which regulate social partnership in the labor field. The authors reveal the social and legal significance of social partnership between employees and employers for the benefit of the sustainable development of the society’s economy, problems related to the establishment and implementation of Russia’s state-legal policy in the modern conditions. The article puts a special emphasis on the analysis of peculiarities related to the development of laws in the constituent entities of Russia on social partnership in the field of social labor on the example of statutory acts adopted in the Stavropol region. In addition, the authors pay sufficient attention to bringing to light the principles of social partnership in the labor field and its primary forms (collective negotiations over the signing of collective contracts and agreements). The article reveals problems that Russia currently faces in pursuing the social partnership policy in the laborfield and substantiates proposals for solving them.